2007
DOI: 10.1080/02713680701624705
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemistry and Electron Microscopy of Retrocorneal Scrolls in Syphilitic Interstitial Keratitis

Abstract: We confirmed the presence of collagens I, III, IV, VI, VIII and proteoglycans in the retrocorneal scrolls lined with attenuated endothelium. Our findings may provide further insight into the pathogenesis of keratopathy in syphilitic interstitial keratitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 11 publications
1
21
0
1
Order By: Relevance
“…However, RCMs also expressed several corneal endothelium marker including VEGF and VEGFR1. This partial expression pattern of corneal endothelial markers suggests the possible involvement of both of endothelial mesenchymal transition in RCM pathogenesis as previously reported (1, 14) and progenitor cell recruitment from other sites as a new concept of pathogenesis of RCM. This finding is supportive of the argument that RCMs do not originate from corneal endothelia.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, RCMs also expressed several corneal endothelium marker including VEGF and VEGFR1. This partial expression pattern of corneal endothelial markers suggests the possible involvement of both of endothelial mesenchymal transition in RCM pathogenesis as previously reported (1, 14) and progenitor cell recruitment from other sites as a new concept of pathogenesis of RCM. This finding is supportive of the argument that RCMs do not originate from corneal endothelia.…”
Section: Discussionsupporting
confidence: 82%
“…Many studies have been conducted to identify the pathogenesis of RCMs (1, 2, 3, 4, 5, 6); however, the results have been largely inconclusive. These past studies have suggested that RCMs are connected to damaged portions of Descemet's membrane and that RCMs grow from the corneal endothelium into the anterior chamber (4, 5, 12, 13, 14, 15). However, these hypotheses are based on the prerequisite that damaged corneas have functional keratocytes and endothelia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The duplication phenomenon is rarely seen in the human eye, although less organized multilayering or formation of new basement membrane is well known. 9,10,19,27,31,34,38 The phenomenon of duplication of DM in the COPLOW database has a moderate frequency. It is seen in cats but not in horses or birds.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Retrocorneal scrolls or scrolling of Descemet’s membrane is a rare finding reported in syphilitic interstitial keratitis. Our literature search identified two cases reported in 1983 and 2001, 2 , 3 and two case series of 14 eyes and five eyes with syphilitic retrocorneal scrolls in 1976 4 and 2007, 5 respectively. The patients in the reported cases underwent penetrating keratoplasty due to pseudophakic bullous keratopathy or corneal opacity and edema.…”
Section: Introductionmentioning
confidence: 99%